Visi Teologis dan Manajemen Pembinaan Calon Imam berdasarkan Ratio Fundamentalis Institutionis Sacerdotalis - Pasati, Yohanes Dwi Penta (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
The purpose of this study is to comprehend the basic guidelines of priestly formation in which priesthood candidates purify their vocation motivation and align it with the priestly vision, which isbased on a theological vision of Christ as the High Priest. This theological vision of Christ as the High Priest is then elaborated specifically in a rule of life for the priesthood candidates. This rule of life is constructed based on six aspects of formation: personality, spirituality, community, intellectual, pastoral, and vocation. After interpreting the theological vision, the priesthood candidates are invited to develop their vocation together in a community of priesthood candidates where they are invited todevelop themselves together in various fields of skills. This is what is called managerial activity, which even in formation, the elements of management affect the lives of the priesthood candidates. Based on this, the priestly formation is based on a formation guideline contained in the Ratio FundamentalisInstitutionis Sacerdotalis formation document. The goal of priestly formation is for the candidates to realize their future identity as priests of Christ. Therefore, in order to achieve this goal, priesthood candidates engage themselves in various activities that lead to the goal of formation. In the management term, this cycle is referred to as management functions. The management function itself consists of planning, organizing, implementing, supervising, and evaluating.